Myomectomy during Caesarean Section: Safety and Feasibility of the Procedure (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective (s): Aim of the study was to evaluate the safety and feasibility of myomectomy during cesarean section.Materials and methods: This prospective observational study was carried out in a private setting at Dhaka city from January 2006 to June 2015. Forty five (45) women with fibroid uterus with pregnancy who needed caesarean section were the target population for this study. Myomectomy was done during caesarean section. Main outcome measures were: difficulty of myomectomy and caesarean section, time needed for operation, per-operative complications, need for blood transfusion, postoperative complications and duration of hospital stay.Results: During the study period total 45 women were found who had pregnancy with myoma and needed caesarean section for various indications. Twenty nine (64.4%) women were of age 26-35 years, 30 (66.7%) were para 0 and in 37 (82%) cases were term pregnancy. In forty one (91.1%) cases myomas were diagnosed preoperatively. Twenty five (55.6%) women had multiple myomas. Commonest site of myoma was body of the uterus (82.2%) and commonest type was intramural (75.6%). Thirty (66.7%) women had myoma of less than 5cm in size. In forty two (93.3%) cases myomectomy was done after delivery of the baby. Myomectomy was successful in all 45 (100%) cases. In thirty (80%) cases caesarean myomectomy was completed within 1 hour. Thirty seven (82.2%) women did not need blood transfusion and thirty eight (84.4%) women had no postoperative complication. Other had minor complications. Forty one (90.1%) women were discharged from hospital within 72 hours of operations.Conclusion: Myomectomy during cesarean section is a safe procedure and it is feasible in almost all cases. Though large scale RCT is needed before giving final conclusion it is not far away when myomectomy during cesarean section will be norm discarding the traditional view of not touching the myoma in pregnancyBangladesh J Obstet Gynaecol, 2015; Vol. 30(1) : 10-14